Histologic and Molecular Patterns in Responders and Non-responders With Chronic-Active Antibody-Mediated Rejection in Kidney Transplants - Sazpinar, Onur; Gaspert, Ariana; Sidler, Daniel; Rechsteiner, Markus; Mueller, Thomas F. (Frontiers in Medicine, 2022)
Introduction There is no proven therapy for chronic-active antibody-mediated rejection (caABMR), the major cause of late kidney allograft failure. Histological and molecular patterns associated with possible therapy responses are not known. Methods Based on rigorous selection criteria this retrospective study identified out of 1027 consecutive kidney transplant biopsies taken between 2008 and 2016 only those with pure, unquestionable caABMR and no other pathologic features. In addition, slopes of filtration pre- and post-treatment as well as biopsy-based anti-rejection treatments were required to differentiate into responders and non-responders. A priori sets of genes reflecting active immune processes of caABMR were defined, including endothelial, inflammatory, cellular, interferon gamma (IFNg) and calcineurin inhibitor (CNI) related-genes. Transcript measurements were performed in stored, formalin-fixed, paraffin-embedded (FFPE) samples using NanoString™ technology. Histology and gene expression patterns of responders and non-responders were compared. Results Therapy responders had a significantly lower peritubular capillaritis score (p=0.028) along with less glomerulitis. In contrast, no single gene discriminated responders from non-responders. Activated genes associated with NK cells and endothelial cells indicated lack of treatment response. A reductionist approach applying very tight criteria to identify caABMR and treatment response excluded the vast majority of clinical ABMR cases. Only 16 out of 139 cases with a written diagnosis of chronic rejection fulfilled the caABMR criteria. Using NanoString™ technology allows high quality transcript measurements even in FFPE samples stored for a long time. Conclusion In caABMR active microvascular injury, in particular peritubular capillaritis, differentiates treatment responders from non-responders. Transcriptome changes in NK cell and endothelial cell associated genes may further help to identify treatment response. However, randomized, placebo-controlled studies with standardized treatments and larger sample sets are necessary to validate biomarkers for treatment response. (ClinicalTrials.gov Number: NCT03430414).